ORGANIZATIONAL CAPACITY AND UTILIZATION OF EVALUATION RESULTS - Okul, Edwin Ochieng (Advances in Social Sciences Research Journal, 2021)
A major concern in programme management, given the potential of programme or project evaluations to inform decision-making, has been how to ensure the results or findings of an evaluation are used for the intended purpose. How information from an evaluation process and/or the products are used in practice and decision making is equally a concern for evaluators. This article presents a research that sought to explore the extent to which organizational capacity impacts the utilization of evaluation findings for programme improvement. Guided by the pragmatic paradigm and informed by the Utilization Focused Evaluation Model and Knowledge Use Theory, the research adopted a descriptive and correlational design using mixed methods. The sample size for this study was 232 project staff from Non-Governmental Organizations (NGOs) in Kisumu Central Sub-County, Kenya. To analyze qualitative data, the open ended responses from key informant interviews were recorded and coded appropriately for further analysis for themes through content analysis and comparative analysis. Frequencies and percentages were calculated to describe the basic characteristics of the quantitative data. To ensure validity and reliability of the research instruments, pilot testing was conducted. Cronbach’s alpha at α = 0.908 was attained as the reliability coefficient of the pre-test instruments. Tests of statistical assumptions were carried out before data analysis to avoid invalidation. A hypotheses H01: Organizational capacity does not significantly influence utilization of evaluation results was tested at α = .05 level of significance and was rejected since P = 0.000 < 0.05. The study findings demonstrate that there is a significant relationship between organizational capacity and the utilization of evaluation results. This research therefore reinforces literature and helps to understand the ways in which organizational capacity influences the utilization of evaluation results. It thus informs the evaluation field of study, fills gaps in the evaluation use literature and contributes to the appreciation of factors that predict and enhance the utilization of evaluation results.